L-serine metabolic regulation and host respiratory homeostasis - Li, Pan; Wu, Xiaoyan; Huang, Yanlan; Qin, Ruijing; Xiong, Pan; Qiu, Yangyang (Frontiers in Cellular and Infection Microbiology, 2025)
L-Serine, a non-essential amino acid (NEAA), can be obtained through diet or in situ synthesis. Functionally, L-serine not only serves as the precursor of other amino acids, lipids, and nucleotides, but also participates in the folate/methionine cycle. An increasing number of studies have demonstrated that L-serine is widely used in the adjuvant therapy of many diseases (e.g., inflammation, infections, fibrosis, and tumors). Here, we summarize the synthesis and metabolism of serine followed by its functions in health and disease. Moreover, we delineate the potential mechanisms whereby L-serine is involved in the occurrence and progression of respiratory diseases. This review aims to summarize the research progress of serine in diseases, propose the problems that need to be solved in the future, and provide guidance for subsequent research and development.